واقع و متطلبات توجه البنوك نحو الخدمات الخضراء دراسة تجارب دولية شمال أروبا(السويد، الدنمارك، وفنلندا أنموذجا) - زينب أهناني; مديحة حمي; يمينة غومة (جامعة الوادي University Of Eloued, 2024)
"ملخص الدراسة: تهدف هذه الدراسة إلى إبراز أهمية توجه البنوك نحو الخدمات الخضراء، وذلك من خلال دراسة إشكالية مهمة تتمحور حول كيفية مساهمة توجه البنوك نحو الخدمات المصرفية الخضراء في تعزيز نشاط المصارف ودفعها لتمويل المشاريع النظيفة، وتحقيق هذا التوجه في شمال أوروبا؟ وتعتمد هذه الدراسة على المنهج الوصفي التحليلي الاستنتاجي بأدواته المختلفة كالوصف، والتحليل حيث تم استعراض لواقع تبني البنوك للخدمات الخضراء في تلك الدول، وتعزيز تمويل مشاريع الطاقة النظيفة، وكيفية تمويل الانتقال الطاقوي باستخدام هيئات ممولة لهذه المشاريع البيئية ومدى تحقيقها لأهدافها. وقد توصلت هذه الدراسة إلى أن الصيرفة الخضراء تعتبر من الموضوعات المعاصرة والمهمة، فقد جاءت نتيجة لتطور الخدمات البنكية من خلال المبادلات والتنويع، والخدمات الخضراء تعتبر أحد آليات تنشيط وتدعيم المشاريع المفيدة للبيئة قصد تحقيق استدامة البنوك ( الاجتماعية، الاقتصادية، والبيئية) لتحقيق الربح و السمعة الجيدة على المدى الطويل، لذلك كان لزاما على البنوك تنفيذ حملات توعية شاملة لتعريف العملاء بفوائد هذه الخدمات وتأثيرها الإيجابي على البيئة مما يساهم في زيادة الطلب عليها وتشجيع الابتكار في مجال الخدمات المصرفية الخضراء من خلال تحديد ميزانية للبحث والتطوير. " "Summary: This study aims to highlight the importance of banks towards green services, through a problematic study that focuses on how banks' contributions towards green services in the field of employment, as shared by new students, can this trend in Northern Europe? This study relies on the simplistic descriptive model with its various tools such as description and analysis, where the reality of green service institutions in those countries was reviewed, their qualifications for simple energy basics, and how to finance energy using funding bodies for these advanced projects and the extent to which they achieve their goals. This study concluded that green banking is considered one of the contemporary and important topics, and has become a result of the development of banking services through exchanges and diversification, and sports are considered one of the reasons for comfort and contribution to the design of bank sustainability projects (economic, social and environmental) to achieve profit and accreditation. On a large scale, it was necessary for the banks to implement comprehensive awareness campaigns to inform customers of the benefits of these services and expand their scope, leading to increased demand for them and encouraging investment in the field of green services by setting the focus on contribution"
مذكرة ماستر
Keywords: الخدمات الخضراء، الصيرفة الخضراء، آليات الصيرفة الخضراء، تجارب شمال أوروبا، البنوك، التنمية المستدامة.; green services; green banking; green banking records; Northern European experiences; banks; social development.